Private Information and Dynamic Bargaining in Supply Chains: An Experimental Study - Davis, Andrew M.; Hyndman, Kyle (Manufacturing and Service Operations Management, 2021)
Problem definition: We conduct a controlled human-subjects experiment in a two-tier supply chain where a supplier’s per-unit production cost may be private information while bargaining with a buyer. Academic/practical relevance: Academically, supply chain studies often assume full-information or highly structured bargaining. We consider private information with dynamic, unstructured bargaining. In practice, a buyer may not know its supplier’s cost exactly and interact with its supplier in a back-and-forth bargaining environment. Thus, understanding how a supplier’s private cost information affects both supply chain outcomes and bargaining is new to the literature and relevant to practice. Methodology: We employ insights from mechanism design to generate restrictions on the space of agreements and solve for a specific bargaining solution under private information to generate precise predictions. These predictions are then tested through a human-subjects experiment. Results: In our experiment, theory predicts that all supplier types should earn at least 50% of total profits when their cost information is private. However, we find that high-cost suppliers earn a disproportionately low share of total profits under private information, 20.16%. We show that this is because buyers, under private information, act as if they are bargaining with the lowest-cost supplier and suppliers do not appear to blame buyers for behaving this way. Based on these findings, we conduct an additional experiment where suppliers have the ability to communicate their private costs to buyers and observe that verifiable disclosure significantly increases profits for high-cost suppliers. Managerial implications: High-cost suppliers actually suffer from having their costs as private information, which runs counter to theory. However, if high-cost suppliers can credibly disclose their costs to buyers, they can significantly increase profits. Lastly, although private information does not lead to more disagreements, negotiations do take longer, which can be costly to firms.